Nuclear expression of the ubiquitin ligase seven in absentia homolog (SIAH)-1 induces proliferation and migration of liver cancer cells - Brauckhoff, Antje; Malz, Mona; Tschaharganeh, Darjus-Felix; Malek, Nisar Peter; Weber, Achim; Riener, Marc-Oliver; Soll, Christopher; Samarin, Jana; Bissinger, Michaela; Schmidt, Jan; Longerich, Thomas; Ehemann, Volker; et al. (Journal of hepatology, 2011)
Background & Aims - Differential expression of tumor-relevant proteins based on aberrant proteasomal degradation may contribute to human (hepato)carcinogenesis. Recently, we identified the E3 ubiquitin ligase seven in absentia homolog (SIAH)-1 as frequently dysregulated in human hepatocellular carcinoma (HCC). We therefore systematically analyzed the expression, functional relevance, as well as possible downstream effectors of SIAH-1 in human liver carcinogenesis. - Methods - SIAH-1 expression was analyzed at the transcript and protein levels in human hepatocarcinogenesis and in HCC cells. Proliferation, apoptosis, and migration of different HCC cell lines were examined after siRNA-mediated inhibition of SIAH-1. In order to identify downstream effectors that mediate SIAH-1 effects, correlative analyses of protein expression profiles were performed. - Results - In HCC tissues both reduction of cytoplasmic SIAH-1 and especially its nuclear accumulation positively correlated with HCC progression. RNA interference revealed that nuclear expression of SIAH-1 predominantly supported HCC cell proliferation and migration while only moderately affecting anti-apoptosis. In de-differentiated human HCCs, nuclear SIAH-1 accumulation significantly correlated with the expression of the transcription factor far-upstream element (FUSE)-binding protein (FBP)-3. In vitro, SIAH-1 positively and indirectly regulated FBP-3 which itself primarily supported HCC cell proliferation. Indeed, high level expression of FBP-3 in human HCCs significantly correlated with reduced overall survival of patients. - Conclusions - Nuclear accumulation of the E3 ubiquitin ligase SIAH-1 supports different pro-tumorigenic cellular processes associated with tumor growth and tumor cell dissemination in human hepatocarcinogenesis. It promotes HCC cell proliferation by at least partly employing the transcription factor FBP-3. Therefore, interference with SIAH-1 activity represents a promising approach to suppress HCC growth.